Concept of Information Service Management Guidance and Counseling - All Habsy, Bakhrudin; Apriliya, Karina; Salsabilla Apriliyana, Gian; Firdaus Az Zahra, Kevina; Mahendra, Wiratama (Riviera Publishing, 2024)
Information services are services that aim to provide knowledge, insight, and understanding to students regarding various aspects that are relevant to their needs, both in the fields of education, career, and personal and social development. Currently, information services in guidance and counseling can be delivered through various media, such as websites, online counseling, and social media platforms, which allow students to access information more easily and quickly. This study aims to apply the Concept of Information Service Management in guidance and counseling through a literature study approach. The research method uses a literature review by compiling data from various accurate sources, such as books and scientific journals that discuss topics related to information services in the context of education, career, and social-personal development of students. Data analysis was carried out using a qualitative approach by taking quotes from opinions that are relevant to the topics discussed. Based on the study, it was revealed that well-organized information service management is able to support students in making important decisions, both in the fields of education and career, and help them understand themselves and their environment. Proper implementation of this information service management can increase the effectiveness of guidance and counseling services as a whole.